INDUSTRIAL DIGITALIZATION AS A TOOL TO INCREASE PRODUCTIVITY EFFICIENCY - Mamurjon Ahmadjonovich Jurabekov (Scholar Express Journals, 2021)
The article is devoted to the analysis of opportunities to increase production efficiency, which opens up in the framework of strategic planning at the state and enterprise levels of the digital economy. The article discusses concepts such as digital economy, development strategy, production efficiency, competitive advantages. It was noted that it is important to take a careful approach to the development of key performance indicators of the enterprise. As a result, the need for a strategic approach to the implementation of digital economy tools is put forward
Keywords: Economic development strategy; digital economy; information technology; labor productivity